More active lecture approaches in science and mathematics : using expert cultural capital to drive change : final report. - Devi Sharma, Manjula; Georgiou, Helen (Dept of Education and Training Australia, 2017)
Final report of a Teaching Fellowship at the University of Sydney. This Fellowship considers the ongoing role of the lecture format within the science and mathematics disciplines and asserts that this format can continue to facilitate student learning as long as appropriate evidenced-based approaches are utilised, such as those falling under the umbrella of active learning. Over 20 years, education experts have developed a number of successful active learning programs that are being selected for use in science and mathematics courses, yet these are being adopted sporadically rather than becoming the norm. Explicit knowledge sharing amongst the different types of academics has been missing as well as guidelines for departments. The Fellowship recommends guidelines which, if implemented, have the capability to shift the culture, not just for transforming the perceived (and real) limitations associated with the traditional lecture format, but for the entire teaching enterprise.